Outcomes of gastrointestinal bleeding in patients with left ventricular assist devices: a tertiary care experience - Taylor, Caren; Bittner, Krystle; Bartell, Nicholas; Aranez, Jose; Alexis, Jeffrey D; Carlson, Beth; Chen, Leway; McNitt, Scott; Kothari, Truptesh; Kaul, Vivek; Kothari, Shivangi (Endoscopy International Open, 2020)
Background and study aims Left ventricular assist device (LVAD) placement is a therapeutic modality for patients with end-stage heart failure. Gastrointestinal bleeding is a common complication following LVAD implantation. The aim of this study was to report our experience in management and outcomes of gastrointestinal bleeding in a large cohort of patients with LVADs. Patients and methods We performed a retrospective review of all patients who underwent LVAD implantation at the University of Rochester Medical Center from January 2008 to June 2017. Data were collected on patient characteristics, clinical aspects of gastrointestinal bleeding events, and procedural interventions. A Cox proportional hazard model was utilized to identify potential risk factors for a gastrointestinal bleeding event. Results During the study period, 345 patients underwent LVAD implantation. Of these, 125 patients (36.2 %) experienced 297 gastrointestinal bleeding events resulting in 533 endoscopic procedures. The diagnostic yield of endoscopy in determining a bleeding source was 49.5 %. If required, therapeutic interventions were successful in achieving homeostasis in 96.2 % of procedures. Our 30-day overall post-procedure adverse event (AE) rate was 6.6 %. Procedure-related (bleeding, infection, and perforation) AEs were very minimal (2.8 %). A Cox proportional hazard model indicated that older age at implant, female sex, African-American race, diabetes mellitus, and pulmonary hypertension were statistically significant predictors of a gastrointestinal bleeding event following LVAD implantation. Conclusions LVAD patients have a high risk of gastrointestinal bleeding. Endoscopy was able to safely locate a bleeding lesion in approximately half of our patients and was successful in treating bleeding lesions in a majority of the cases.